2021
DOI: 10.1371/journal.pone.0253841
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c is inversely associated with thyroid cysts in a euthyroid population: A cross-sectional study

Abstract: Anti-thyroid peroxidase antibody (TPO-Ab) is revealed to be inversely associated with thyroid cysts among euthyroid population. TPO-Ab causes autoimmune thyroiditis by bolstering thyroid inflammation. Therefore, at least partly, absence of thyroid cysts could indicate latent thyroid damage. Since participants with subclinical hypothyroidism are reported to have higher HbA1c than normal healthy controls, HbA1c could be inversely associated with thyroid cysts through a mechanism reflecting latent thyroid damage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The major nding of the present study is a signi cant inverse association between thyroid cysts and CKD in subjects with systolic hypertension, even though no signi cant associations were observed in subjects without systolic hypertension. Because a previous study reported noticeable increases in thyroglobulin concentrations of thyroid cyst uid [12] and thyroglobulin plays a crucial role in thyroid hormone synthesis [13], the presence of thyroid cysts could affect the levels of thyroid hormone activity [1,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The major nding of the present study is a signi cant inverse association between thyroid cysts and CKD in subjects with systolic hypertension, even though no signi cant associations were observed in subjects without systolic hypertension. Because a previous study reported noticeable increases in thyroglobulin concentrations of thyroid cyst uid [12] and thyroglobulin plays a crucial role in thyroid hormone synthesis [13], the presence of thyroid cysts could affect the levels of thyroid hormone activity [1,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with thyroid cysts are typically older than those without thyroid cysts [ 8 , 9 , 30 , 31 ]. Therefore, thyroid cysts could be formed during the aging process, which is related to decreasing demand for thyroid hormone [ 30 , 31 ]. Since thyroid cyst fluid is rich in thyroglobulin [ 11 ], thyroid cysts might act as storage of thyroglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…Since thyroid cyst fluid is rich in thyroglobulin [ 11 ], thyroid cysts might act as storage of thyroglobulin. Thus, thyroid cysts might have a beneficial influence on thyroid hormone secretion when necessary [ 8 , 9 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods used in the present study, including thyroid function evaluation, have been described elsewhere [ 9 , 16 , 17 ]. A trained interviewer obtained information on clinical characteristics, such as history of thyroid disease, glucose-lowering medication use, and smoking and drinking habits.…”
Section: Methodsmentioning
confidence: 99%